Opportunities, Challenges and Creative Teaching Practices of New International and Local Recruits in Hong Kong - Paula Hodgson (Athens Institute for Education and Research, 2019)
Internationalization in higher education in Hong Kong has brought many enriched learning opportunities for students, because international recruits create an alternative learning culture that embraces global perspectives and international research to the curriculum. However, those new to teaching and with non-Asian backgrounds may experience a steeper learning curve as they adjust to a new culture, systems and expectations while working in Hong Kong. Of about 80% local students, educators need to find creative strategies to facilitate them to have interactions and collaborations with non-local students, 15% of whom are from mainland China and have different learning habits. In addition, they have to manage teaching undergraduate and postgraduate programs, which have students from diverse knowledge and working experiences. Twenty-five recruits from social sciences and humanities participated in the study and their reflections on their teaching experiences were analysed using NVivo 11. Solutions on meeting the challenges, good teaching practice and unresolved issues are discussed.